Cultural and Religious Diversity in Early Childhood Education Implications of Socialization and Education for the Geographies of Childhood - Knoblauch, Christoph (Religions, 2023)
Cultural and Religious Diversity in ECE is discussed from multiple perspectives and influenced by different parameters. In this context, culturally and religiously sensitive education faces various dynamic and conflictual challenges, such as different comprehensions of the concepts of culture and religion or current transformations in society. Social spaces such as kindergartens play a major role in offering the potential for diversity to be experienced and reflected in the context of socialization and education. Focusing on the manifold relations between cultural and religious diversity in education, this paper discusses evaluation findings from a qualitative study in the German Early Education sector. Perspectives from children, parents, and educators on the implications of socialization and education for the geographies of childhood are presented with a special focus on options for culturally and religiously sensitive education. The empirical findings, therefore, focus on experiences and assessments from different participants in the field of ECE, offering a multiperspective view on the topic. The study uses semi-structured qualitative interviews and content-based evaluation, interviewing over 200 children, educators, and parents in group interviews. The results are discussed in categories such as socialization of children, competencies of educators, underlying pedagogical concepts, experiential learning, and others. In this context, the paper offers an in depth discussion of the potential of a culturally and religiously sensitive education and the role of communities and religious institutions. Against this backdrop, the question discussed is how these results can be constructively implemented to improve the constructive perception and the usage of educational spaces in ECE.